Potential forest fire during the long dry season Province Riau & Jambi - Hawam, Mochamad Emil; Aulady, Mohamad Ferdaus Noor (Calamity: A Journal of Disaster Technology and Engineering, 2024)
Background: Air pollution is a very serious problem nowadays. Air pollution can be caused by the problem of haze from forest fires that occurred in 2015 & 2019 in Province Riau & Jambi. The worst conditions occurred in the period 1997-1998 and in 2006-2007. In 2015 & 2019 the haze conditions returned to the 1997 period. Province Riau & Jambi contributed to the largest hotspots in forest fires compared to North Sumatra or Kalimantan. The increase in the haze that has continued for the past three months is very worrying because the haze is getting worse and thicker, making the visibility of the affected areas even smaller. The purpose of this research to know the capabilities being run the Riau provincial government has been in control of who impressed off guard because repeated continuously, and whether factors constr ai nts and deﬁenc e i nﬂu enci ng th e c apab i li ti es of th e Province Riau & Jambi government. Method: Descriptive research is research that aims to describe, describe and analyze existing events and aims to obtain information about the impact of the haze in Province Riau & Jambi with existing theories so that it can be used in mitigation in different places. Findings: The urgency in this study to see why the Province Riau & Jambi government off guard so persistent, because the capabilities of the system and the process will involve considering the ﬁre that occurred not once or twice only. Conclusion: The main causes of forest and peatland fires in Riau are human activities, such as the use of fire for land clearing and agricultural practices, combined with natural conditions like dry land and extreme hot weather. These fires significantly impact human health, social interactions, and the environment, necessitating critical awareness among farmers to act responsibly and monitor fire spread to prevent future losses. Novelty/Originality of this article: By analyzing the inhibiting factors and definitions that influence local government capacity, this study opens new insights into the complexity of environmental disaster management involving interactions between human activities, natural conditions, and institutional capacity.